2003
DOI: 10.1021/ef020179u
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Modeling of Coal/Agricultural By-Product Blends

Abstract: There is renewed interest worldwide in the production of sustainable energy from renewable sources, such as biomass, aimed mainly at the decrease of fossil fuels use. Except for its potential to be CO2 “neutral” during combustion, biomass has a low sulfur content and a high volatile concentration:  these characteristics favor clean combustion conditions. The knowledge of the kinetics of biomass pyrolysis and combustion is important for the control of such thermochemical processes. The main objective of this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
47
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 34 publications
7
47
3
Order By: Relevance
“…Several authors have observed interactions between the components of coal and biomass blends [10,37], while others have reported additive behaviour [38][39][40][41][42][43]. Table 3 shows the kinetic parameters (E, k 0 and ψ) determined from the data obtained at the three heating rates (5, 10 and 15 K min -1 ) for all the char samples together with the coefficients of determination, R 2 , for each model and char sample.…”
Section: Interactions Between the Components Of The Blendsmentioning
confidence: 99%
“…Several authors have observed interactions between the components of coal and biomass blends [10,37], while others have reported additive behaviour [38][39][40][41][42][43]. Table 3 shows the kinetic parameters (E, k 0 and ψ) determined from the data obtained at the three heating rates (5, 10 and 15 K min -1 ) for all the char samples together with the coefficients of determination, R 2 , for each model and char sample.…”
Section: Interactions Between the Components Of The Blendsmentioning
confidence: 99%
“…10,[12][13][14][15][16][17][18][19][20][21][22] For the description of the present data set of three samples at four heating programs, six partial peaks were necessary. Their parameters and characteristics are listed in Table 7.…”
Section: Model Assuming First Order Kinetics For the Partial Reactionsmentioning
confidence: 99%
“…A wide range of activation energies has been reported in the literature of biomass materials. 10,[12][13][14][15][16][17][18][19][20][21][22][23]40 The Details on the Handling of Parameters m() and T. As described above, the magnitude of the m() and T parameters were constrained into physically meaningful ranges by choosing appropriate  values in eq 8.…”
Section: Model Assuming First Order Kinetics For the Partial Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] The biomass fuels and raw materials contain a wide variety of pyrolyzing species. Even the same chemical species may have different reactivity if their pyrolysis is influenced by other species in their vicinity.…”
Section: Introductionmentioning
confidence: 99%